2017
DOI: 10.1136/vr.104154
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy drug handling in first opinion small animal veterinary practices in the United Kingdom: results of a questionnaire survey

Abstract: To investigate how first opinion small animal veterinary surgeons in the UK handled chemotherapeutic agents, a questionnaire was distributed at the 2014 British Small Animal Veterinary Association congress and by internet. Chemotherapy was regularly offered by 70.4 per cent of the respondents. Gold standards defined according to available guidelines for safe handling of antineoplastic drugs were poorly followed by general practitioners with only 2 per cent of respondents complying with all of them. Dedicated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This involves having updated safe handling guidelines and policies that reflect current evidence. Edery 53 conducted a study in veterinary practices and found that implementation of stricter guidelines was an important factor in reducing exposure to cytotoxic agents. 53 This was similar to studies that suggest updated policies may improve safe handling behaviours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This involves having updated safe handling guidelines and policies that reflect current evidence. Edery 53 conducted a study in veterinary practices and found that implementation of stricter guidelines was an important factor in reducing exposure to cytotoxic agents. 53 This was similar to studies that suggest updated policies may improve safe handling behaviours.…”
Section: Resultsmentioning
confidence: 99%
“…Edery 53 conducted a study in veterinary practices and found that implementation of stricter guidelines was an important factor in reducing exposure to cytotoxic agents. 53 This was similar to studies that suggest updated policies may improve safe handling behaviours. 44,54 Several stakeholders concurred with this finding.…”
Section: Poor Trainingmentioning
confidence: 99%
“…Owners of animals undergoing chemotherapy may be poorly informed and despite the fact that chemotherapy is becoming a more common therapy there have been no large scale studies on the prevalence and incidence of side-effects associated with this treatment [32]. Of additional concern is that the public health risks associated with the use of chemotherapeutic agents may not be given adequate attention in veterinary practice [43]. Importantly, cancer-associated pain has been found to be underdiagnosed in companion animals leading to inadequate pain management and diminished quality of life [4,44].…”
Section: Discussionmentioning
confidence: 99%
“…To match this increase, general veterinary practitioners are becoming more confident with the techniques of chemotherapy administration and knowledge of available protocols. A recent survey found that nearly 70 per cent of general veterinary practitioners were offering chemotherapy regularly to their patients (Edery 2017). Commonly used chemotherapy protocols in general practice are COP/CHOP (vincristine, cyclophosphamide, prednisolone ± doxorubicin) for lymphoma and vinblastine/prednisolone for mast cell tumour disease.…”
mentioning
confidence: 99%